The differences in temperament-character traits, suicide attempts, impulsivity, and functionality levels of patients with bipolar disorder I and II - Izci, Filiz; Fınıklı, Ebru; Zincir, Serkan; Bozkurt Zincir, Selma; Iris Koc, Merve (Neuropsychiatric disease and treatment, 2016)
The primary aim of this study was to compare the differences in temperament-character traits, suicide attempts, impulsivity, and functionality levels of patients with bipolar disorder I (BD-I) and bipolar disorder II (BD-II). Fifty-two BD-I patients and 49 BD-II patients admitted to Erenköy Mental and Neurological Disease Training and Research Hospital psychiatry clinic and fifty age- and sex-matched healthy control subjects were enrolled in this study. A structured clinical interview for Diagnostic and Statistical Manual of Mental Disorders, 4th Edition Axis I Disorders, Temperament and Character Inventory, Barrett Impulsiveness Scale-11 (BIS-11), Hamilton Depression Inventory Scale, Young Mania Rating Scale, and Bipolar Disorder Functioning Questionnaire (BDFQ) were administered to patients and to control group. No statistically significant difference in sociodemographic features existed between the patient and control groups (P>0.05). Thirty-eight subjects (37.62%) in the patient group had a suicide attempt. Twenty-three of these subjects (60.52%) had BD-I, and 15 of these subjects (39.47%) had BD-II. Suicide attempt rates in BD-I and II patients were 60.52% and 39.47%, respectively (P<0.05). Comparison of BD-I and II patients with healthy control subjects revealed that cooperativeness (C), self-directedness (Sdi), and self-transcendence (ST) scores were lower and novelty seeking (NS1 and NS2), harm avoidance (HA4), and reward dependence (RD2) subscale scores were higher in patients with BD-I. When BD-I patients were compared with BD-II patients, BIS-11 (attention) scores were higher in patients with BD-II and BIS-11 (motor and nonplanning impulsivity) scores were higher in patients with BD-I. According to BDFQ, relations with friends, participation in social activities, daily activities and hobbies, and occupation subscale scores were lower and taking initiative subscale scores were higher in patients with BD-I. Social withdrawal subscale scores were higher in patients with BD-II. In our study, NS, HA, and RD scores that may be found high in suicide attempters and Sdi scores that may be found low in suicide attempters were as follows: NS1, NS2, HA4, and RD2 subscale scores were high and Sdi scores were low in patients with BD-I, suggesting a higher rate of suicide attempts in this group of patients. In addition, C and Sdi scores that indicate a predisposition to personality disorder were significantly lower in patients with BD-I than patients with BD-II and healthy controls, suggesting a higher rate of personality disorder comorbidity in patients with BD-I. Higher impulsivity and suicidality rates and poorer functionality in patients with BD-I also suggest that patients with BD-I may be more impulsive and more prone to suicide and have poorer functionality in some areas.